Assessment of computer task performance (ACTP) of children and youth with intellectual and developmental disability. - Danial-Saad, Alexandra; Tamar Weiss, Patrice L; Schreuer, Naomi (Disability & Rehabilitation: Assistive Technology, 2012)
The aims of this study were to assess the reliability and validity of the Arabic translation of the Assessment of Computer Task Performance (ACTP) when used for children with Intellectual and Developmental Disabilities (IDD) and to determine the relationship between participants' performance when using an adapted pointing device and the teacher's satisfaction of their performance. Thirty boys and girls, Arabic speakers, 6- 21 years old, who had moderate IDD, participated in the study. Two expert occupational therapists used the ACTP to evaluate the performance of five standardized timed computer tasks. The Quebec User Evaluation of Satisfaction with Assistive Technology was used to evaluate the teachers' satisfaction with the prescribed pointing device. The sample in the current study performed slower than typically developing children and youth, and slower than participants with motor impairments, examined in previous studies. Differences were found in performance time between girls and boys, and between three diagnostic subgroups. The participants' success scores of computer performance correlated significantly with the teacher's satisfaction with the prescribed pointing device. Demonstration of the validity and reliability of the Arabic version of the ACTP-Child enables wider use of this tool which is now available in four languages and diverse cultural settings and disability populations, including children and youth with significant IDD. [Box: see text].